Nichts als Strohfeuer? Eine kritische Analyse des wirtschaftspolitischen Assignments im "Neuen Konsens" mit Hilfe eines makrooekonometrischen Politiksimulationsmodells der Schweizer Volkswirtschaft - Jochen Hartwig (Intervention. Zeitschrift fuer Ökonomie / Journal of Economics, 2004)
– The paper is concerned with the traditional "assignment" to be found in many textbooks that holds central bankers responsible for inflation – and inflation only – while government politicians are recommended to care for the short-term stabilisation of the economy (or not to interfere at all, respectively). Building on monetary and fiscal policy simulations done with a macroeconometric model of the Swiss economy, possible long-term real effects of monetary policy are established. Also, a potential role for fiscal policy in the control of inflation is located. Since macroeconometric modelling is now widely regarded as being outmoded, special care is taken to argue that neither the seminal "Lucas critique" nor more recent time series approaches can be said to have overridden the traditional approach.
Keywords: C51; C53; E17; E52; E63; 330